Preparation and thermal shock behavior of nanoscale MgAl2O4 spinel-toughened MgO-based refractory aggregates - Gu, Qiang; Zhao, Fei; Liu, Xinhong; Jia, Quanli (Ceramics international, 2019)
Nanoscale MgAl2O4 (MA) spinel-toughened MgO-based refractory aggregates were prepared by firing lightly calcined magnesia powder and some nanoscale Al2O3 (≤50 nm) particles at high temperature. The effects of various amounts of nanoscale Al2O3 powder on the phase composition, microstructure, physical properties and thermal shock resistance (TSR) of the prepared MgO-based refractory aggregates were investigated. The results showed that the optimum nanoscale Al2O3 powder addition was 10 wt%, and the nanoscale Al2O3 particles reacted with MgO during firing and formed nanoscale MA creating reactive sintering, which contributed to significant increasing in density and cold strength of the prepared aggregates. The thermal mismatch between nano-MA and MgO could produce microcracks created toughening effect, leading to improvement in TSR of the prepared aggregates. And the formed nano MA grains pinned in MgO grain boundaries and on MgO grain surfaces would lead to microcracks deflection and absorbing much more fracture energy, further improving the TSR. The obtained aggregates were trial used in MgO-C slide plate materials, and thermal shock resistance of the materials was improved.